2019
DOI: 10.1111/dme.14061
|View full text |Cite
|
Sign up to set email alerts
|

Use of remote monitoring with continuous glucose monitoring in young children with Type 1 diabetes: the parents’ perspective

Abstract: Aim Remote monitoring with continuous glucose monitoring (CGM) in children with Type 1 diabetes mellitus has recently become available, but little is known about caregivers’ experiences of its use, particularly in younger children. The aim of this study was to explore parents’ everyday experiences of using this technology. Methods The parents of children with Type 1 diabetes diagnosed for > 1 year, aged 2–12 years were invited to participate in a semi‐structured interview. Interviews were the second phase of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 23 publications
1
43
2
Order By: Relevance
“…In Italy, the widespread use of CGM and flash glucose monitoring among people with T1D allowed these patients to be remotely connected to the clinic through the cloud, but the use of these technologies in children and adolescents have also bridged the gap between school and family care capacities. Recently, it was demonstrated that parents of kindergarten and school children reported the usefulness and the effectiveness of remote monitoring and CGM to control glucose excursions (48). The COVID-19 pandemic has forced children and parents to spend many hours together at home, bringing back diabetes care to parents.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the widespread use of CGM and flash glucose monitoring among people with T1D allowed these patients to be remotely connected to the clinic through the cloud, but the use of these technologies in children and adolescents have also bridged the gap between school and family care capacities. Recently, it was demonstrated that parents of kindergarten and school children reported the usefulness and the effectiveness of remote monitoring and CGM to control glucose excursions (48). The COVID-19 pandemic has forced children and parents to spend many hours together at home, bringing back diabetes care to parents.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that newer technologies, such as continuous glucose monitors and closedloop systems, are likely to help further ease the burden of diabetes management. For example, use of continuous glucose monitors may lessen parental anxiety due to the device alerting them to hypo-and hyperglycaemia [41], while those able to monitor their child's glucose data remotely may experience improved sleep and greater lifestyle freedoms [42,43]. Similarly, while user evaluations of closed-loop systems have mainly involved older participant groups with type 1 diabetes and/or their parents [44][45][46][47][48], preliminary trials involving very young children suggest that this technology can help parents feel less burdened by diabetes management tasks and facilitate better sleep [49].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the reduction in hypoglycemia anxiety in children using CGM both separately and pump augmented [ 17 , 20 , 21 ]. Pre-hypoglycemic alarms are a warning.…”
Section: Discussionmentioning
confidence: 95%
“…Night-time rest is disturbed by frequent alarms, the need to check blood glucose levels, and anxiety about hypoglycemia [ 20 ]. In a study conducted by Burckhardt et al, parameters assessed among caregivers of preschool children were also related to the parents’ sleep—better sleep was highlighted during CGM use [ 21 ]. In our analysis, we also noted an improvement in the sleep of caregivers.…”
Section: Discussionmentioning
confidence: 99%